The Potential Role of Claudins in Regulation of Metastasis and Development of Drug Resistance in Breast Cancer - Patadia, Hemantkumar; Priyadarshini, Ankita; Ranade, Jay; Gangawane, Ajit (Clinical Cancer Drugs, 2020)
Background: Breast Cancer is a recurrent problem across the world. According to a report, breast cancer has the second highest mortality rate in women globally. Despite having an advanced degree of chemotherapy, resistance is developed against the therapies. Studies showed that anthracyclins like doxorubicin used in the treatment of breast cancer are found to develop resistance, which is not easy to identify. Mutations in the tumor suppressor gene P53 are associated with the primary resistance to doxorubicin and thus inducing an early relapse of breast tumors. Resistance against Doxorubicin is not identifiable easily. Development of resistance and metastasis of tumors are the two processes that cannot be separated from each other. It is widely known that endothelium has a major role in controlling metastasis and tumor cell invasion. Endothelial cells express different adhesion molecules during recruitment of leukocytes in localized area, which is called leukocyte extravasation or diapedesis, or leukocyte trans endothelial migration (LEM). LEM (leukocyte trans endothelial migration) plays crucial role in the inflammation of breast cancer tissues. Objective: Predicting the role of deregulation of claudins in leukocyte trans endothelial migration in breast cancer metastasis and resistance. Methods: The breast cancer proteomic metadata was collected and compared among the common candidates. The enrichment analysis of those common candidates was performed using a network analyst. Results: The analysis of breast cancer genes obtained from dbDEPC showed probable involvement of 4 candidate genes belonging to the claudin family. Claudins are responsible for the migration of an increased amount of leukocytes in the breast tumor region, which increases the inflammation and may contribute to worsening the disease progression. Conclusion: We believe these candidates also contribute in the development of resistance to chemotherapy.
Keywords: metastasis